Effects of floor space and removal of corn distillers dried grains with solubles on heavy weight pig performance - Lerner, Anne Bonner (Kansas State University, 2019)
This dissertation is comprised of 5 chapters consisting of a study evaluating space allowance and marketing strategies for pigs raised to 160 kg, three experiments evaluating the impact of removing corn distillers dried grains with solubles (DDGS) from finishing pig diets, four studies evaluating the use of medium chain fatty acids (MCFA) as a mitigation strategy for porcine epidemic diarrhea virus (PEDV), and development of a swine-specific undergraduate research program. In Chapter 1, four treatments were evaluated with decreasing space allowance from 1.17 to 0.71 m2/pig with only one final marketing event, plus two treatments with restricted space allowance and four or three marketing events. Increasing space allowance via increased initial pen inventory increased average daily gain (ADG), decreased average daily feed intake (ADFI), and reduced feed efficiency (G:F). Marketing pigs 3 or 4 times improved G:F compared with to the similar treatment with only one marketing event but resulted in similar weight marketed per pen. In chapter 2, pigs were switched from diets containing corn DDGS to corn- and soybean-meal based diets (CSBM) starting at 76 d prior to market. As time consuming CSBM increased, ADG and final BW increased and G:F improved. Average daily feed intake decreased with increasing time after dietary switch to CSBM. Hot carcass weight increased and iodine value decreased with increasing time after DDGS removal from diets. Chapter 3 also evaluated the removal of corn DDGS from finishing pig diets but utilized two seasonal marketing strategies. Regardless of marketing strategy, switching pigs from DDGS to CSBM resulted in increased carcass yield and decreased iodine value, yet live growth performance was marginally impacted. In chapter 4, four experiments were conducted to evaluate the efficacy of applying MCFA to swine feed on detection and infectivity of PEDV. Applying chemical mitigants both prior to and post-PEDV inoculation was effective at reducing PEDV detection via quantitative real time reverse transcriptase polymerase chain reaction (qRT-PCR). When tested individually and in combination and applied before viral inoculation, caproic and caprylic acid appeared to provide the greatest reduction of detectable genetic material. The addition of a 1:1:1 blend of C6:C8:C10 at 0.5% and 0.3% C8 prevented infection in in vivo bioassay. Lastly, chapter 5 presents a model to develop a species-specific undergraduate research program in the context of a swine nutrition program that is currently in use at Kansas State University. This program utilizes both graduate students and faculty to provide mentorship and has several project types that vary in level of student involvement. The program is designed to provide a comprehensive research experience, with an emphasis on including the student in pre- and post-trial activities beyond data collection. A majority of students that complete the undergraduate research program enter graduate or veterinary degree programs upon completion of their undergraduate work and cite undergraduate research as a critical step in their career selection process and professional development.
Keywords: Swine; Undergraduate research; Porcine epidemic diarrhea virus; Corn distillers dried grains with solubles; Heavy weight pigs; Medium chain fatty acids